Antidepressant Effects of Repetitive Transcranial Magnetic Stimulation Over Prefrontal Cortex of Parkinson's Disease Patients With Depression: A Meta-Analysis - Zhou, Liang; Guo, Zhiwei; Xing, Guoqiang; Peng, Haitao; Cai, Mengjie; Chen, Huaping; McClure, Morgan A.; He, Lin; Xiong, Liangwen; He, Bin; Du, Fei; Mu, Qiwen (Frontiers in Psychiatry, 2019)
Objective: The purpose of this meta-analysis was to investigate the anti-depression effects of repetitive transcranial magnetic stimulation (rTMS) over the prefrontal cortex (PFC) of patients with Parkinson’s disease (PD) and to determine the optimal rTMS parameters, such as the intensity, frequency and the delivered pattern of rTMS stimulation. Methods: EMBASE, PubMed, Web of Science, MEDLINE, and Cochrane data bases were researched for papers published before March 12, 2018. Studies investigating the anti-depression effects of rTMS over PFC in patients with PD were considered. The main outcomes were depression scales scores such as Self-Rating Depression Scale (SDS), Hamilton Rating Scale for Depression (HAM-D), and Beck Depression Inventory (BDI). The mean effect size was estimated by calculating the standardized mean difference (SMD) with 95 % confidence interval (CI) by using fixed or random effect models as appropriate. Results：Nine studies containing 137 PD patients with depression were included. The results showed significant anti-depression effect of rTMS over PFC in depressed PD patients (SMD = -0.55; p = 0.02). The subgroup analysis showed a better therapeutic effect of 5.0 Hz frequency rTMS (SMD = -0.90; p = 0.003) than that of less than 1.0 Hz frequency rTMS and greater than or equal to 10.0 Hz-frequency rTMS. Additionally, applied to supra-threshold of the rest motor threshold (RMT), rTMS produced significant anti-depressive effects (p < 0.0001, SMD = -0.82), whereas stimulation which used intensity of 90 % or 100 % of the RMT did not. Furthermore, rTMS treatment conducted in discontinuous days were more effective than those conducted in continuous days (SMD = -0.54; p = 0.03; vs SMD = -0.54; p = 0.11 respectively). Conclusions: The results demonstrate significant anti-depressive effect of rTMS over PFC in PD patients with depression. 5 Hz rTMS with supra- threshold intensity conducted in discontinuous days might appear to be more effective than other treatment strategies. Future studies with larger number of participants are needed to validate the current findings and to expand the optimal rTMS protocols.